Observed changes to the stability of a subsea pipeline caused by seabed mobility. (1st December 2018) - Leckie, Simon H.F.; Draper, Scott; White, David J.; Cheng, Liang; Griffiths, Terry; Fogliani, Antonino
Abstract: High resolution bathymetry combined with structural modelling is used to estimate changes in the on-bottom stability of an offshore pipeline due to scour and sedimentation over an 11 year period. Detailed observations of post-lay embedment changes have been combined with the pipeline structural characteristics and an elastic-plastic model of soil resistance to estimate the vertical and horizontal stability of the pipeline using a finite difference solution to the beam bending equation. Application of the design approach indicates that post-lay increases to the critical (break-out) velocity of 1–2 m/s occur along the full 19 km of surveyed pipeline due to scour and sedimentation, which act to reduce load and increase soil resistance. The rate at which this increase in stability occurs with time is found to vary along the pipeline, and is dependent on the mechanism of pipeline lowering (i.e. whether the pipe lowered due to sagging into widely spaced scour holes, or by sinking into the shoulders between many closely spaced scour holes). By incorporating sediment transport into the pipeline design, the present results suggest potential for significant improvements in pipeline on-bottom stability and associated reductions in minimum required specific gravity and/or secondary stabilisation. Highlights: Seabed mobility driven changes to pipeline embedment are observed in the field. The resulting changes to pipeline on-bottom stability are quantified. Increases in critical velocity of 1–2 m/s are calculated for a steady current. The amount of increase is dependent on the mechanism of pipeline lowering. Increased soil resistance and hydrodynamic shielding are both shown to be important.